Reconstructing China the peaceful development, economic growth, and international role of an emerging super power - Li, Jingzhi 1943- (McGraw-Hill, 2014)
"This fascinating, in-depth look at China's new and rapidly changing role in the world focuses on the critical choices China must make to ensure sustainable economic growth.All signs show that China's diplomacy is facing unprecedented changes, among which opportunities and challenges coexist. As power is redistributed globally, China finds it is at a crossroad. By comparing possible modes of the rise of great powers, Re-Constructing China introduces the necessity of China's peaceful development and growth and explains how the nation can achieve it in the most effective way possible. China is attempting to become a great power of a new breed and in its development must maintain sustained economic growth and explore a revitalization of its cultural confidence.Li Jingzhi is a professor at Renmin University of China. He has served as dean of Institute of International Relations at Renmin University of China and editor-in-chief of Teaching and Research".